Josephine Letitia Denny Fairfield (1885–1978): Pushing the boundaries of medicine. (November 2014) - Garrett, Emily
Letitia Fairfield – doctor, lawyer, public health worker, feminist and war worker – was a woman of surprising contradictions. She displayed some eccentric tendencies that sometimes did not sit comfortably with her role as a medical professional; she was, for example, a believer in witchcraft and a convert to Roman Catholicism. However, she made great contributions to medicine throughout her active career and did so during a period in which female access to medical education was limited. Few of her female or male peers received such respect or oversaw such change. Despite pushing contemporary professional boundaries and reaching a level of seniority unusual for female doctors of her era, however, Letitia was, whether through choice or through convention, channelled into traditionally female areas of medicine. Thus, her medical success arguably was due not only to her motivation and capability but also because she represented no real competition to men.